The interplay of low identification, psychological detachment, and cynicism for predicting counterproductive work behaviour - Tong, Jiajin (2020)
Prior research suggests that psychological detachment buffers the detrimental effects of negative work events and stressors on employees’ subsequent performance and well-being. This, however, assumes that employees are motivated to reengage in their work following detachment, which may not always be true. Our paper examines the potential dark side of psychological detachment by exploring its moderating effects on the relationship of low organisational identification with counterproductive work behaviour (CWB) via cynicism toward work. Based on self-discrepancy theory, we argue that detachment strengthens the link from low identification to cynicism because it reinforces the psychological distance of lowly identified employees with the organisation and provides them with additional resources to more deeply reflect on their mismatch with their organisation, thus generating stronger feelings of doubt and distrust that characterise cynicism. We also hypothesise that detachment strengthens the relation from cynicism to CWB, because detachment reinforces personal separation from work in cynical employees and because cynical employees may leverage their replenished resources to fuel deviant acts. Multi-wave data collected from two field samples support our hypotheses. We discuss the implications of our study and propose future research directions.